2021
DOI: 10.1002/pros.24119
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two different low‐intensity shockwave therapy frequency protocols for nonbacterial chronic prostatitis/chronic pelvic pain syndrome: A two‐arm, parallel‐group randomized controlled trial

Abstract: Background: Despite encouraging results, the optimal low-intensity shockwave therapy (LiST) protocol in patients with chronic prostatitis/chronic pelvic pain syndrome (CPPS) remains unknown. We conducted a two-arm, parallel-group, randomized controlled trial aiming to compare the efficacy and safety of six LiST sessions applied once or twice weekly.Methods: Fifty patients with CP/CPPS type IIIb were randomly assigned to six LiST sessions once (Group A, n = 25) or twice weekly (Group B, n = 25). Both groups fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…More specifically, 2,000 impulses were delivered to the corpora cavernosa, 2,000 to the crura cavernosa and 1,000 to the penile hila based on a protocol developed by our research team. 12–14…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, 2,000 impulses were delivered to the corpora cavernosa, 2,000 to the crura cavernosa and 1,000 to the penile hila based on a protocol developed by our research team. 12–14…”
Section: Methodsmentioning
confidence: 99%
“…Также I. Mykoniatis и соавт. (2021) [27] провели РКИ для сравнения эффективности и безопасности 6 сеансов низкоинтенсивной ЭУВТ (ARIES 2 и Smart Focus probe, Dornier MedTech GmbH, Германия) у 50 па -…”
Section: обзорная статья / Reviewunclassified
“…Через 1 и 3 мес после курса лечения ЭУВТ значительно улучшились показатели по опросникам NIH-CPSI, IPSS, МИЭФ-5 в обеих группах (р <0,001). При сравнении эффективности лечения ЭУВТ статистически значимой разницы между двумя группами не зафиксировано [27].…”
Section: обзорная статья / Reviewunclassified
“…They compared between group of 1 session per week and 2 sessions per week for overall 6 sessions applied and resulted in statistically insignificant for both groups compared (p-value>0.05) but statistically significant compared to the baseline (p-value< 0.05). 11…”
Section: Clinical Protocolmentioning
confidence: 99%
“…However all ESWT clinical protocols in this systematic review have shown significant improvement of CPSI scores compared to baseline. 11 ESWT effect on pain domain From 3 different type of ESWT machinery (EP, EM, PE), all of them shared the same effect on pain domain from CPSI scoring system. Study from Ghazi et al, using EP Roland Pagani ES.WT machine showed significant improvement of pain symptom.…”
Section: Eswt Treatment Protocolmentioning
confidence: 99%